Characterization of Surface Acidity of Maredan Clay Catalyst Activated with Sulfuric Acid Using Boehm Titration and Pyridine Adsorption Method - . Nurhayati (New Trends in Physical Science Research Vol. 6, 2022)
The acid or base of a solid surface is a fascinating element of surface structure that is crucial in the fields of ion exchange and heterogeneous catalysis. The use of natural clay as a heterogeneous catalyst is due to its acidity, however the acidity of the natural clay is not sufficient to be used especially in the esterification of free fatty acids into biodiesel. The objectives of this study were to synthesize catalyst of Maredan clay activated with sulfuric acid and to characterize the surface acidity by the Boehm titration and pyridine vapour adsorption method. The impregnation method was used to activate Maredan clay with various concentrations of sulfuric acid (0.5, 1, 2, and 3 M). The results showed that with the addition of sulfuric acid concentration, the total acidity of the clay catalyst increased with a maximum yield of 0.6483 mmol/g obtained by using Boehm titration method and 1.1137 mmol/g catalyst by using pyridine vapor adsorption method. The acid site of the Maredan clay catalyst activated by sulfuric acid was identified as the Lewis acid site using FTIR analysis of the pyridine vapour adsorption spectra.